The teaching of theatre and new technologies: methodological possibilities of the intermediate scene (Revista NUPEART, 2023)
The text discusses methodological possibilities that mayarise from the relationship between theater and new technologies, through experimentation from the assumptions of the intermedial scene, against the backdrop of the current school routine formed by the generation of digital natives whose contact with digital technology devices is increasing.
Keywords: theater teaching; new technologies; intermedia scena